PELATIHAN PEMBUATAN KERUPUK SARI DAUN BAMBU UNTUK MEMANFAATKAN HASIL POTENSI DESA DAN MENINGKATKAN PEREKONOMIAN WARGA DUSUN PETISSARI DESA BABAKSARI KECAMATAN DUKUN KABUPATEN GRESIK (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Bamboo which has not been developed so far will only add to the stack of bamboo leaves organicwaste. People who do not know the benefits of more than bamboo will certainly burn the wasteproduced by bamboo plants. Bamboo leaves are known to contain various active substances, namelypolysaccharides, chlorophyll, flavonoids, vitamins, amino acids, and microelements able to overcomeseveral types of diseases, including gout, prevent heart disease, cancer, overcome intestinal worms,and launch menstruation. Babaksari villagers, especially petissari hamlets, still do not know thatbamboo leaves can be used as food preparations, one of which is that bamboo leaves can be used asprocessed crackers, which we know that crackers are foods that are mandatory in Indonesiansociety. With the innovation of new products, this bamboo leaf cracker can add to the income of thevillagers of Babaksari. The aim of this project is to, among others, strive to improve the economy ofthe Babaksari village community, increase the sale value of bamboo leaves through various processed village snacks, Establish business groups / communities as a form of product sustainability.Key Word :Bamboo, organic